Investigating Anxiety in an Indonesian EFL Speaking Classroom - RAIS ABIN; Hariadi Syam (Universitas Negeri Makassar, 2019)
Abstract. This research aimed to explore the kinds of anxiety experienced by the students in learning speaking, and to examine the causes of the anxiety in learning speaking. This research employed descriptive qualitative method. The subjects of this research were 36 students consisting 19 females and 17 males selected to be research participants through conveniently selected sampling. The data of this research were collected by online questionnaire, and interview. The obtained data were analyzed in three major phases namely data reduction, data display, and conclusion. The result of the research revealed three kinds of anxiety experienced by the students in learning speaking namely trait anxiety, situational-specific anxiety, and state anxiety. Furthermore, the causes of speaking anxiety were communication apprehension, test anxiety, and fear of negative evaluation.